Diagnóstico situacional turístico de la ciudad de Ventanas Provincia de Los Ríos - Castro Yaguana, Andrea Angelica (2020)
The present investigative work focuses on studying the tourist situational diagnosis of the city of Ventanas, since the citizens do not know places, projects, and other factors that help the tourist growth of the town. To collect the information, this study was base don the analytical and observational method through a general analysis of what happens in the city of Ventanas focused on the tourist environment through documented and diagnostic research base don the survey and observation, same that helped determine the current tourism situation. Determining that citizens must be informed of new tourist events that occur in the city through social networks, new, radio, flyers and others.